2015
DOI: 10.1038/bjc.2015.412
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma-expressed CD70 is involved in invasion and metastasis

Abstract: Background:CD70 is a costimulatory molecule of the tumour necrosis factor family expressed in activated immune cells and some solid tumours. In lymphocytes CD70 triggers T cell-mediated cytotoxicity and mitogen-activated protein kinase phosphorylation.Methods:We evaluated the expression of CD70 in biopsies and melanoma cell lines. Using melanoma cell lines positive or not for CD70, we analysed CD70 function on melanoma progression.Results:We report CD70 expression in human melanoma cell lines and tumour cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 21 publications
1
29
0
Order By: Relevance
“…CD70 is a costimulatory molecule member of the tumor necrosis factor family that is expressed on activated immune cells. We have described that this protein of which tumoral expression is regulated by RhoA GTPases, promote CD70 positive melanoma cells invasiveness by a new non‐immunological mechanism . Altogether our data show that statins and Rho inhibition positively regulate MHC class I and costimulatory molecules expression on melanoma cells.…”
Section: Statins and Rho Gtpases Inhibition Modify The Expression Of supporting
confidence: 58%
See 1 more Smart Citation
“…CD70 is a costimulatory molecule member of the tumor necrosis factor family that is expressed on activated immune cells. We have described that this protein of which tumoral expression is regulated by RhoA GTPases, promote CD70 positive melanoma cells invasiveness by a new non‐immunological mechanism . Altogether our data show that statins and Rho inhibition positively regulate MHC class I and costimulatory molecules expression on melanoma cells.…”
Section: Statins and Rho Gtpases Inhibition Modify The Expression Of supporting
confidence: 58%
“…Unexpectedly we have demonstrated that GGTases inhibitors down regulate PD‐L1 expression induced by IFN‐γ on melanoma cells improving the ability of Rho inhibition to promote melanoma immunogenicity. Finally we have reported for the first time CD70 expression on human melanoma surface . CD70 is a costimulatory molecule member of the tumor necrosis factor family that is expressed on activated immune cells.…”
Section: Statins and Rho Gtpases Inhibition Modify The Expression Of mentioning
confidence: 91%
“…Although we are the first to describe this effect by CD70-positive CAFs, CD70 overexpression on tumor cells has already been linked with migration in non-small cell lung cancer, melanoma and glioblastoma. [28][29][30] In the latter, knockdown of the CD70 gene resulted in a decrease in genes associated with tumor epithelial-mesenchymal transition (EMT) such as CD44 and SOX2. Also in CRC, overexpression of CD44 has been shown to drive EMT changes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been described that CD70 is not only a ligand but contains an underlying signalling cascade whereby activation leads to MAPK activation, RhoE overexpression and cytoskeletal changes, driving migration in melanoma. 29 It has been demonstrated that targeting the CD70/CD27 axis can inhibit an effective anti-tumor immune response by three modes of action: accumulation of Tregs, T-cell apoptosis and skewing T-cell towards T-cell exhaustion. 13 Increased numbers of Tregs have been particularly found in the presence of CD70-expressing tumor cells due the expression of CD27 on the Tregs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to regulating host immune activation/suppression, CD70 may also play a direct role in metastasis of melanoma cells, where a cytosolic monomeric form of the protein appears to correlate with poor invasion and metastatic capacities. In contrast, increased levels of trimeric CD70 at the outer membrane can activate MAPK/PhoE signalling and may instead enhance melanoma cell invasiveness [54]. In light of the recent report that exosomal PD-L1 can promote immunosuppression and likely inhibit immune checkpoint blockade therapy in melanoma [55], it is possible that CD70/CD27 in EVs may perform similar roles in patients with lung tumours and other types of cancer.…”
Section: Several Of These Proteins Have Been Reported In Other Contexmentioning
confidence: 99%